MECHANISMS FOR ENHANCING THE TRANSPARENCY AND EFFECTIVENESS OF PUBLIC ADMINISTRATION IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF THE MANGYSTAU REGION - Abdieva S.R.; Saimagambetova G.А.; Pernebekkyzy N. (Foundations and Trends in Modern Learning, 2025)
The article examines the mechanisms for enhancing the transparency and effectiveness of public administration in the context of sustainable development of the Mangystau Region. The relevance of the study is determined by a new stage of political and institutional reforms in the Republic of Kazakhstan aimed at decentralizing the system of state and local self-government. Based on the amendments and additions introduced by the Constitutional Law “On Elections in the Republic of Kazakhstan” dated May 25, 2021, a mechanism for the direct election of akims (mayors) of towns of district significance, settlements, and rural districts has been implemented. This initiative represents a concrete step toward democratic renewal outlined in President K.-Zh. K. Tokayev’s Address to the Nation “Kazakhstan in a New Reality: The Period of Action.” The article considers the new model of local self-government as an important tool for increasing the openness and accountability of the state power system, as well as for strengthening civic participation in regional development. Using the example of the Mangystau Region, the author analyzes the institutionalization of feedback between authorities and society at the local level, the improvement of decision-making quality through direct elections of akims, and the assessment of the effectiveness of local development programs. The study results show that enhancing the transparency and effectiveness of public administration requires strengthening the professional and managerial capacity of local self-government bodies, establishing effective communication with the public, and ensuring digital openness in decision-making processes. Reforms in this direction contribute to the development of a culture of trust and responsibility in the implementation of regional development strategies